Pemaknaan al-Din dan al-Islam dalam Qur’an A Reformist Translation - Iwanebel, Fejrian Yazdajird (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
Abstract: This paper highlights the ideas on the meaning of religion within Quran: A Reformist Translation, a contemporary work that promotes a reformist paradigm of Quranic interpretation. On the methodological framework, their exegesis lies on the Qur’an alone, which means to let the Qur’anexplainstheir self within their logic and linguistic features. They refuse the hierarchical and epistemic authority of the clergy in interpreting the Qur’an. Further, they have also rejected the authority of hadis. With this theoretical framework, they do not interpret al-dînas religion, but as a system. They also do not interpret Islam as a proper name related to the religion of Muhammad, but as a mindset and action which lies on the system of peacemaking and peaceful surrendering. This kind of interpretation theoretically makes a shifting orientation of the verse which generally tends to theology, dogmatic, and exclusive become humanist, dialogue and inclusive. Keywords: Qur’anic translation; reformist, al-dîn; al-islâm. Abstrak: artikel inimembahas tentang gagasan makna agama dalam Quran: A Reformist Translation, sebuah karya terjemah Alquran kontemporeryang menawarkan pandangan baru dalam melihat teks dengan semangat reformis. Kerangka metodologis penafsiran mereka adalah al-Qur’an alone, yaitu membiarkan Alquran menjelaskan dirinya sendiri dengan logika kebahasaannya. Mereka menolak otoritas ulama sebagai epistemologi tafsirnya, termasuk dalam hal ini hadis. Dengan kerangka ini, mereka memaknai al-dîntidak sebagai agama, melainkan sebagai sistem. Demikian juga dengan al-islâm, mereka tidak menafsirkan kata tersebut sebagai nama agama tertentu, melainkan sebuah mindsetdan aksi yang berpijak pada sistem kepasrahan dan kedamaian. Penafsiran inisecara teoritismerubah orientasi ayat yang semula bersifat teologis, dogmatis dan eksklusif menjadi humanis, dialogis dan inklusif. Kata Kunci: Terjemah Alquran; reformis; al-dîn; al-islâm.